Education’s New Normal: From Classroom to Digital Screen in Post-COVID-19 Bangladesh - Hasan, Md Mehedi; Chowdhury, Md Solaiman Chowdhury; Syed Muhammod Ali Reza; Moral, Iqbal Hossain; Md Enamul Haque (South Asian Journal of Social Sciences and Humanities, 2024)
This study investigates the transition from traditional in-person education to online learning in post-COVID-19 Bangladesh, with a focus on how user experience, attitude effect motivation, and acceptance influence the efficacy of digital education. Using a sample of 200 respondents, the study employed correlation, regression, t-tests, and chi-square analyses to understand these relationships. The correlation analysis revealed a strong positive relationship between attitude effect motivation and acceptance of online learning suggesting that enhancing the quality of online platforms can significantly boost students’ motivation. User experience was moderately correlated with acceptance underscoring the importance of user-friendly design in fostering greater acceptance. However, the weaker correlation between user experience and motivation indicates that improving user experience alone may not directly increase motivational attitudes, highlighting the multifaceted nature of online learning acceptance. Regression analysis found that learning platform usability was the strongest predictor of acceptance, followed by user experience and motivation. T-test results revealed no significant difference in user experience across genders, suggesting that both male and female students engage similarly with online learning platforms. A chi-square test indicated no significant association between location and institute type, prompting further research into other factors influencing institutional choice. These findings offer actionable insights for educational institutions and online learning providers, emphasizing the importance of improving platform usability, enhancing motivation, and developing inclusive digital learning environments.